The stand - King, Stephen, 1947-; Dee, Ruby.; Lowe, Rob.; Sinise, Gary.; Ferrer, Miguel, 1954-2017; Ringwald, Molly; Davis, Ossie; Sheridan, Jamey; Walston, Ray, 1917-2001.; Frewer, Matt, 1958-; Paramount Pictures Corporation; CBS Broadcasting Inc. ([United States] : Paramount Picture, 2013)
Originally aired as a television mini-series, this all-star filmization of Stephen King's gripping epic of good versus evil chronicles the episodic adventures of a disparate group of people who struggle to reestablish civilization after a man-made catastrophe wipes out most of the world's population. The world abruptly ends when a deadly virus accidentally escapes from a government sponsored biological warfare laboratory. Soon people are dropping like flies from the plague.
Title from container.
Originally aired on television in 1994.
Release date: Jun. 18, 2013.
Ruby Dee, Rob Lowe, Gary Sinise, Miguel Ferrer, Molly Ringwald, Ossie Davis, Jamey Sheridan, Ray Walston, Matt Frewer, Laura San Giacomo, Corin Nemec.
Rating: Not rated CHV rating: 14A.
DVD, full screen; Dolby Digital.
Keywords: Good and evil -- Drama; Fiction television programs; Feature films; Video recordings for the hearing impaired